Modeling carbon allocation strategies for high-yielding perennial crops - Erin Kilbane; Timothy Crews; Lee DeHaan; Michael Grillo; Brian Ohsowski; Ray Dybzinski (European Journal of Agronomy, 2025)

Calculating Nitrogen Uptake Rates in Forests: Which Components Can Be Omitted, Simplified, or Taken from Trait Databases and Which Must Be Measured In Situ? - Ray Dybzinski; Ella Segal; M. Luke McCormack; Christine R. Rollinson; Rosemary Mascarenhas; Perry Giambuzzi; Jamilys Rivera; Lucien Fitzpatrick; Caylin Wiggins; Meghan G. Midgley (Ecosystems, 2024)

Short‐term plant–soil feedback experiment fails to predict outcome of competition observed in long‐term field experiment - Noelle G. Beckman; Ray Dybzinski; David Tilman (Ecology, 2023)
Mounting evidence suggests that plant–soil feedbacks (PSF) may determine plant community structure. However, we still have a poor understanding of how predictions from short‐term PSF experiments compare with outcomes of long‐term field experiments involving competing plants. We conducted a reciprocal greenhouse experiment to examine how the growth of prairie grass species depended on the soil communities cultured by conspecific or heterospecific plant species in the field. The source soil came from monocultures in a long‐term competition experiment (LTCE; Cedar Creek Ecosystem Science Reserve, MN, USA). Within the LTCE, six species of perennial prairie grasses were grown in monocultures or in eight pairwise competition plots for 12 years under conditions of low or high soil nitrogen availability. In six cases, one species clearly excluded the other; in two cases, the pair appeared to coexist. In year 15, we gathered soil from all 12 soil types (monocultures of six species by two nitrogen levels) and grew seedlings of all six species in each soil type for 7 weeks. Using biomass estimates from this greenhouse experiment, we predicted coexistence or competitive exclusion using pairwise PSFs, as derived by Bever and colleagues, and compared model predictions to observed outcomes within the LTCE. Pairwise PSFs among the species pairs ranged from negative, which is predicted to promote coexistence, to positive, which is predicted to promote competitive exclusion. However, these short‐term PSF predictions bore no systematic resemblance to the actual outcomes of competition observed in the LTCE. Other forces may have more strongly influenced the competitive interactions or critical assumptions that underlie the PSF predictions may not have been met. Importantly, the pairwise PSF score derived by Bever et al. is only valid when the two species exhibit an internal equilibrium, corresponding to the Lotka–Volterra competition outcomes of stable coexistence and founder control. Predicting the other two scenarios, competitive exclusion by either species irrespective of initial conditions, requires measuring biomass in uncultured soil, which is methodologically challenging. Subject to several caveats that we discuss, our results call into question whether long‐term competitive outcomes in the field can be predicted from the results of short‐term PSF experiments.

Nitrogen, water, and phosphorus uptake as functions of fine-root mass in greenhouse microcosms of Poa pratensis - Ray Dybzinski; Natalie Taylor; Megan Prosser; Olivia Niosi; Madeline Demo; Erin Kilbane (Plant Ecology, 2021)

How are nitrogen availability, fine‐root mass, and nitrogen uptake related empirically? Implications for models and theory - Ray Dybzinski; Angelo Kelvakis; John McCabe; Samantha Panock; Kanyarak Anuchitlertchon; Leah Vasarhelyi; M. Luke McCormack; Gordon G. McNickle; Hendrik Poorter; Clare Trinder; Caroline E. Farrior (Global Change Biology, 2019)
Understanding the effects of global change in terrestrial communities requires an understanding of how limiting resources interact with plant traits to affect productivity. Here, we focus on nitrogen and ask whether plant community nitrogen uptake rate is determined (a) by nitrogen availability alone or (b) by the product of nitrogen availability and fine‐root mass. Surprisingly, this is not empirically resolved. We performed controlled microcosm experiments and reanalyzed published pot experiments and field data to determine the relationship between community‐level nitrogen uptake rate, nitrogen availability, and fine‐root mass for 46 unique combinations of species, nitrogen levels, and growing conditions. We found that plant community nitrogen uptake rate was unaffected by fine‐root mass in 63% of cases and saturated with fine‐root mass in 29% of cases (92% in total). In contrast, plant community nitrogen uptake rate was clearly affected by nitrogen availability. The results support the idea that although plants may over‐proliferate fine roots for individual‐level competition, it comes without an increase in community‐level nitrogen uptake. The results have implications for the mechanisms included in coupled carbon‐nitrogen terrestrial biosphere models (CN‐TBMs) and are consistent with CN‐TBMs that operate above the individual scale and omit fine‐root mass in equations of nitrogen uptake rate but inconsistent with the majority of CN‐TBMs, which operate above the individual scale and include fine‐root mass in equations of nitrogen uptake rate. For the much smaller number of CN‐TBMs that explicitly model individual‐based belowground competition for nitrogen, the results suggest that the relative (not absolute) fine‐root mass of competing individuals should be included in the equations that determine individual‐level nitrogen uptake rates. By providing empirical data to support the assumptions used in CN‐TBMs, we put their global climate change predictions on firmer ground.

Predicting vegetation type through physiological and environmental interactions with leaf traits: evergreen and deciduous forests in an earth system modeling framework - Ensheng Weng; Caroline E. Farrior; Ray Dybzinski; Stephen W. Pacala (Global Change Biology, 2017)
Earth system models are incorporating plant trait diversity into their land components to better predict vegetation dynamics in a changing climate. However, extant plant trait distributions will not allow extrapolations to novel community assemblages in future climates, which will require a mechanistic understanding of the trade‐offs that determine trait diversity. In this study, we show how physiological trade‐offs involving leaf mass per unit area ( LMA ), leaf lifespan, leaf nitrogen, and leaf respiration may explain the distribution patterns of evergreen and deciduous trees in the temperate and boreal zones based on (1) an evolutionary analysis of a simple mathematical model and (2) simulation experiments of an individual‐based dynamic vegetation model (i.e., LM 3‐ PPA ). The evolutionary analysis shows that these leaf traits set up a trade‐off between carbon‐ and nitrogen‐use efficiency at the scale of individual trees and therefore determine competitively dominant leaf strategies. As soil nitrogen availability increases, the dominant leaf strategy switches from one that is high in nitrogen‐use efficiency to one that is high in carbon‐use efficiency or, equivalently, from high‐ LMA /long‐lived leaves (i.e., evergreen) to low‐ LMA /short‐lived leaves (i.e., deciduous). In a region of intermediate soil nitrogen availability, the dominant leaf strategy may be either deciduous or evergreen depending on the initial conditions of plant trait abundance (i.e., founder controlled) due to feedbacks of leaf traits on soil nitrogen mineralization through litter quality. Simulated successional patterns by LM 3‐ PPA from the leaf physiological trade‐offs are consistent with observed successional dynamics of evergreen and deciduous forests at three sites spanning the temperate to boreal zones.

Increased forest carbon storage with increased atmospheric CO 2 despite nitrogen limitation: a game‐theoretic allocation model for trees in competition for nitrogen and light - Ray Dybzinski; Caroline E. Farrior; Stephen W. Pacala (Global Change Biology, 2015)
Changes in resource availability often cause competitively driven changes in tree allocation to foliage, wood, and fine roots, either via plastic changes within individuals or through turnover of individuals with differing strategies. Here, we investigate how optimally competitive tree allocation should change in response to elevated atmospheric CO 2 along a gradient of nitrogen and light availability, together with how those changes should affect carbon storage in living biomass. We present a physiologically‐based forest model that includes the primary functions of wood and nitrogen. From a tree's perspective, wood is an offensive and defensive weapon used against neighbors in competition for light. From a biogeochemical perspective, wood is the primary living reservoir of stored carbon. Nitrogen constitutes a tree's photosynthetic machinery and the support systems for that machinery, and its limited availability thus reduces a tree's ability to fix carbon. This model has been previously successful in predicting allocation to foliage, wood, and fine roots along natural productivity gradients. Using game theory, we solve the model for competitively optimal foliage, wood, and fine root allocation strategies for trees in competition for nitrogen and light as a function of CO 2 and nitrogen mineralization rate. Instead of down‐regulating under nitrogen limitation, carbon storage under elevated CO 2 relative to carbon storage at ambient CO 2 is approximately independent of the nitrogen mineralization rate. This surprising prediction is a consequence of both increased competition for nitrogen driving increased fine root biomass and increased competition for light driving increased allocation to wood under elevated CO 2 .

Neighborhoods have little effect on fungal attack or insect predation of developing seeds in a grassland biodiversity experiment - Noelle G. Beckman; Ray Dybzinski; G. David Tilman (Oecologia, 2014)

Resource limitation in a competitive context determines complex plant responses to experimental resource additions - Caroline E. Farrior; David Tilman; Ray Dybzinski; Peter B. Reich; Simon A. Levin; Stephen W. Pacala (Ecology, 2013)
Almost all models of plant resource limitation are grounded in either one or both of two simple conceptual models: Liebig's Minimum Hypothesis (LMH), the idea that plants are limited by the resource in shortest supply, and the Multiple Limitation Hypothesis (MLH), the idea that plants should adjust to their environment so that all essential resources are equally limiting. Despite the differences in their predictions, experiments have so far failed to discriminate between them. In a simple factorial nitrogen and water addition experiment in a Minnesota grassland, we observed shifts in allocation that, as in previous studies, are not all explained by a single theory. We found that leaf biomass responded positively to nitrogen additions but did not respond to water additions. We found that fine‐root biomass increased in response to water additions, but only at low nitrogen levels, and that fine‐root biomass decreased in response to nitrogen additions, but only at high water levels. To understand these responses we built a physiologically based model of plant competition for water, nitrogen, and space to predict plant allocation to fine roots and leaves. Critically, we include in our model the inherent variability of soil moisture and treat light, water, and nitrogen as resources with distinct mechanistic roles. Experimental results showed that plants were nitrogen and water limited. The model explains the experimental results, under conditions of co‐limitation, as follows. Foliage increases with nitrogen additions but not water additions because leaf construction is constrained by nitrogen uptake. When water is added, plants spend a larger fraction of the growing season limited by light (and effectively nitrogen) than by water. Thus, water additions cause fine‐root biomass to increase because of the increased importance of nitrogen limitation. The response of fine‐root biomass to water additions decreases with nitrogen additions because these additions reduce nitrogen limitation. In general, our results are explained by sequential resource limitation. The rate of carbon assimilation may be limited by a single resource at any one moment, but the identity of the limiting resource(s) changes throughout the growing season.

Game theory and plant ecology - Gordon G. McNickle; Ray Dybzinski (Ecology Letters, 2013)
The fixed and plastic traits possessed by a plant, which may be collectively thought of as its strategy , are commonly modelled as density‐independent adaptations to its environment. However, plant strategies may also represent density‐ or frequency‐dependent adaptations to the strategies used by neighbours. Game theory provides the tools to characterise such density‐ and frequency‐dependent interactions. Here, we review the contributions of game theory to plant ecology. After briefly reviewing game theory from the perspective of plant ecology, we divide our review into three sections. First, game theoretical models of allocation to shoots and roots often predict investment in those organs beyond what would be optimal in the absence of competition. Second, game theoretical models of enemy defence suggest that an individual's investment in defence is not only a means of reducing its own tissue damage but also a means of deflecting enemies onto competitors. Finally, game theoretical models of trade with mutualistic partners suggest that the optimal trade may reflect competition for access to mutualistic partners among plants. In short, our review provides an accessible entrance to game theory that will help plant ecologists enrich their research with its worldview and existing predictions.

Seed and microsite limitation in a late-successional old field: the effects of water, adults, litter, and small mammals on seeds and seedlings - Ray Dybzinski; David Tilman (Plant Ecology, 2012)

Soil fertility increases with plant species diversity in a long-term biodiversity experiment - Ray Dybzinski; Joseph E. Fargione; Donald R. Zak; Dario Fornara; David Tilman (Oecologia, 2008)